2013
DOI: 10.1007/s10661-013-3291-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variation in the hydrochemistry of Tawa River, Central India: effect of natural and anthropogenic factors

Abstract: Tawa River is the biggest left bank tributary of the Narmada, the largest west-flowing river of the Indian peninsula. Central India enjoys a tropical climate, is highly urbanized, and the river flow is mostly controlled by monsoon; a large part of the population depend on rivers for their livelihood. Spatial and temporal variations in the hydrochemistry of the Tawa River were studied based on seasonal sampling along the course of the river and its tributaries. The study is important because not much data exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This difference can be attributed to the river water being greatly diluted during the monsoon season by the large amounts of rainfall, which has a low EC (Meybeck and Helmer 1989). Decreased solute concentrations during the monsoon have indeed been reported in a previous study of the Songkhram river (Satrawaha et al 2009) as well as for monsoon rivers in India (Mehto and Chakrapani 2013;Kumarasamy et al 2014;Thomas et al 2014).…”
Section: Discussion Longitudinal and Transverse Hydrochemical Trendsmentioning
confidence: 63%
“…This difference can be attributed to the river water being greatly diluted during the monsoon season by the large amounts of rainfall, which has a low EC (Meybeck and Helmer 1989). Decreased solute concentrations during the monsoon have indeed been reported in a previous study of the Songkhram river (Satrawaha et al 2009) as well as for monsoon rivers in India (Mehto and Chakrapani 2013;Kumarasamy et al 2014;Thomas et al 2014).…”
Section: Discussion Longitudinal and Transverse Hydrochemical Trendsmentioning
confidence: 63%
“…This indicating the tendency of waters to dissolve more of these mineral phases and/or suggesting that these mineral phases are less abundant in the corresponding host rock [58] [59]. However, according to [60], the IS value in the Tawa River Central India situated in the humid tropical zone varied from …”
Section: Saturation Indices (Si)mentioning
confidence: 99%
“…It was found that water chemistry in the Sutlej river is mainly determined by weathering of carbonates besides silicate minerals. The ratio of (Na + + K + )/ T Z + is used to assess the contribution of cations via silicate weathering (Mehto and Chakrapani 2013;Stallard and Edmond 1987). This average ratio was 1.07 during pre-monsoon 2017, 2.02 during post-monsoon 2017, 1.60 during pre-monsoon 2018 and 1.33 during post-monsoon 2018.…”
Section: Factors Controlling the Hydrochemistry Of The Sutlej Rivermentioning
confidence: 99%